2021
DOI: 10.1007/s12350-019-01810-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quantitative CMR perfusion imaging by comparison with simultaneous 15O-water-PET

Abstract: Background. We assessed the quantitative accuracy of cardiac perfusion measurements using dynamic contrast-enhanced MRI with simultaneous 15 O-water PET as reference with a fully integrated PET-MR scanner.Methods. 15 patients underwent simultaneous DCE MRI and 15 O-water PET scans at rest and adenosine-stress on an integrated PET-MR scanner. Correlation and agreement between MRI-and PET-based global and regional MBF values were assessed using correlation and Bland-Altman analysis.Results. Three subjects were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Both 15 O-water and 13 N-ammonia require the presence of an on-site cyclotron as a high upfront investment because of the short half-lives of both tracers (2 min and 9 min, respectively). By contrast, Tc-MIBI-SPECT 66,[189][190][191][192] . Note that the 82 Rb and 99m Tc curves overlap.…”
Section: Key Points For Spectmentioning
confidence: 99%
“…Both 15 O-water and 13 N-ammonia require the presence of an on-site cyclotron as a high upfront investment because of the short half-lives of both tracers (2 min and 9 min, respectively). By contrast, Tc-MIBI-SPECT 66,[189][190][191][192] . Note that the 82 Rb and 99m Tc curves overlap.…”
Section: Key Points For Spectmentioning
confidence: 99%
“…These subjects underwent both rest and adenosine-induced stress scans in one session, as previously described. 20 , 21 Ten of the 24 subjects additionally underwent DST imaging as part of the original protocol, which were used for method development (“DST-CAD”). The remaining 23 subjects in the comparison with CMR were diagnosed with asymptomatic moderate-severe or severe mitral- or aortic regurgitation and were consecutively included into an on-going prospective outcome study.…”
Section: Methodsmentioning
confidence: 99%
“…These subjects underwent both rest and adenosine-induced stress scans in one session, as previously described. 20 , 21 Ten of the 24 subjects additionally underwent DST imaging as part of the original protocol, which were used for method development (“DST-CAD”).…”
Section: Methodsmentioning
confidence: 99%
“…In a small study of 15 patients, Kero et al assessed 15 O-water PET-MRI myocardial blood flow and found a good correlation and moderate agreement with simultaneous dynamic contrast-enhanced MRI assessments of myocardial blood flow. 12 Further work is required to assess how PET-MRI myocardial perfusion can be integrated with the other structural and functional information available from MRI imaging (Fig. 3).…”
Section: Myocardial Perfusionmentioning
confidence: 99%